Therapeutic effectiveness of bone marrow-derived mesenchymal stem cell administration against acute pulmonary thromboembolism in a mouse model. Issue 5 (May 2015) - Peng, Xiaochun; Li, Jiansha; Yu, Xiangyuan; Tan, Rubin; Zhu, Liping; Wang, Jun; Wang, Rongshuai; Gu, Guoqiang; Liu, Qian; Ren, Liang; Wang, Chen; Hu, Qinghua
Abstract Instruction Acute pulmonary thromboembolism (APTE) is a common clinical condition associated with significant morbidity and mortality. Although promising, bone marrow-derived mesenchymal stem cell (BMSC) treatment for thrombus resolution remains controversial. The therapeutic effectiveness of BMSC against APTE has not been evaluated. This study aims to determine whether BMSCs administration is effective in mouse model. Materials and Methods Therapeutic efficacy of female and male BMSCs were evaluated by applying serial sectioning analysis method for the whole lungs of APTE mice and calculating each thrombus size in volume. Plasmid construction and stable transfection were used to manipulate expression of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) in both genders of BMSCs. Western blot were performed to detect GAPDH and urokinase plasminogen activator expression in BMSCs. Results Our data showed, 1) compared with non-serial sectioning method, the serial sectioning method detected more thrombi, larger size ranges of thrombus area, and the volume of each individual thrombus. 2) BMSCs significantly decreased the thrombi size in APTE mice, with female BMSCs superior to male ones. 3) female BMSCs showed a higher GAPDH protein level and manipulations of GAPDH expression in female or male BMSCs profoundly affected their therapeutic efficacies as well as urokinase plasminogen activator expression. Conclusion This study indicates serial-sectioning analysis method is necessary for evaluating APTE and provides strong evidences for BMSCs possessing therapeutic effectiveness against APTE, with female BMSCs superior to male counterparts. GAPDH played a critical role in the superior function of female BMSCs, possibly by regulating the expression of urokinase plasminogen activator.